Isu-Isu Kritis Historiografi di Era Digital: Analisis Narasi Sejarah pada Media Sosial - Yulia Citra; Etmi Hardi (Lembaga Yasin AlSys, 2026)
Digital historiography has received attention in various studies alongside the development of information technology and social media. However, studies that specifically discuss changes in historical authority, narrative legitimacy, the reproduction of collective memory, and the spread of historical disinformation on social media remain relatively limited. This study aims to analyze how social media shapes historical narratives and to identify various critical issues that emerge in historiographical practice in the digital era. This study uses a qualitative approach with a qualitative content analysis design combined with digital ethnography. The research data were obtained from 150 historical contents and 3,500 user comments on TikTok, Instagram, YouTube, Facebook, and X platforms selected through purposive sampling. Data were collected through digital documentation and non-participant observation, and were then analyzed using thematic analysis comprising coding, categorization, theme development, and data interpretation. The results show five main findings, namely the increasing democratization of historical narrative production, the dominance of popularity over academic authority as a source of legitimacy, the simplification and fragmentation of historical events, the reproduction of collective memory through digital interaction, and the emergence of disinformation and contestation of historical narratives in social media spaces. These findings also show that social media has transformed historiographical practice from a model centered on academic institutions toward a more participatory and open model. The conclusion of this study affirms the importance of historical literacy and digital literacy in addressing the dynamics of historical knowledge production in the social media era. The implications of the study include strengthening digital historiography theory, developing studies on public history and collective memory, and formulating historical education strategies that are more adaptive to technological transformation. This study also opens opportunities for further research on the influence of algorithms and artificial intelligence on the formation of digital historical narratives.